A Production Process of Extract from the Root of Vietnamese Purple Morinda Officinalis How - Van Dung Trinh; Thi Thu Hang Ta; Van Hung Pham (Journal of Technical Education Science, 2024)
Highly concentrated extracts, known as extracted preparations, are collected by evaporating or drying solutions containing biologically active substances (BASs) found in herbs or animal parts through a leaching process with the assistance of appropriate solvents. Generally, highly concentrated extracts derived from the herbs are produced through two primary stages: (1) leaching BASs from the herbs using suitable solvents, and (2) evaporating or drying the prepared solution to obtain the final product. The leaching process is a crucial step that significantly influences recovery efficiency, product quality, and production costs. In this work, the operating conditions of a leaching system were investigated to extract BASs from MO’s root (MO = Morinda officinalis How), which are the main components in the highly concentrated extract of MO. The results indicate that the maximum yield of BASs dissolved in an ethanol solution reaches 57.3% from MO powder (dimensions approximately 0.56 to 0.58 mm), corresponding to an ethanol solution of 60% (v/v), a temperature of 60 °C, and a leaching time of 6 hours. Based on these findings, a production process for the highly concentrated extracts from Vietnamese purple MO has been established, aiming to create a facilely used product chain, thereby enhancing the value of this rare medicinal plant.